Implementation of Government Regulation Number 11 of 2017 in The Making Transparency Candidate Recruitment of Civil Servants in Custody in The Formation of Position Guard Regional Office Ministry of Justice And Human Rights of Central Java - Pudyastuti Kusuma Wardhani (Jurnal Daulat Hukum, 2018)
Implementation of Recruitment CPNS ideal and transparent according to Regulation No. 11 Of 2017 is the presence of Planning Phase Phase Announcement Jobs Stage Applying Stage Selection Selection Result Announcement. Best Criteria for Carers Formation Resistivity employess employess must have a stock that is as well able to practice martial rules are rules which should not be violated in accordance with Government Regulation No. 11 of 2017 on Civil Service Management. Recruitment obstacles in the implementation employess employess are determining criteria to be spelled out in the system of administration of an application the Selection CAT whose implementation in BKN only have a few units of computers alone is not proportional to the number of applicants who apply,Physical criteria employess formation detainee guards should be done by the competent authorities Observation Physical and skills tested by the examiner should be done by an expert interview. Efforts are being made in resolving these obstacles are Selection of administration should be carried out independently with the online system by providing value criteria that are not limited to academic Exams CAT is done online with the preparation by the recipient employees ooportunity should be tested by the parties who have expertise in physical testing and competent to do so Implementation does not have Standard Operating (SOP) that is in determining the best criteria for the formation of candidates for Civil Servants guard prisoners.Keywords: Employess Recruitment Guard Prisoner.